2011
DOI: 10.1098/rspb.2011.1543
|View full text |Cite
|
Sign up to set email alerts
|

When mothers make sons sexy: maternal effects contribute to the increased sexual attractiveness of extra-pair offspring

Abstract: Quality differences between offspring sired by the social and by an extra-pair partner are usually assumed to have a genetic basis, reflecting genetic benefits of female extra-pair mate choice. In the zebra finch ( Taeniopygia guttata ), we identified a colour ornament that is under sexual selection and appears to have a heritable basis. Hence, by engaging in extra-pair copulations with highly ornamented males, females could, in theory, obtain genes for increased offspring attractivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 65 publications
6
33
0
1
Order By: Relevance
“…The high levels of extra-pair paternity and intraspecific broodparasitism recorded in our study were similar to other studies conducted in zebra finches in captive aviaries (Burley et al, 1996;Forstmeier et al, 2011;Schielzeth and Bolund, 2010;Tschirren et al, 2012), and considerably higher than levels recorded in the wild (Birkhead et al, 1990;. This difference may be a further manifestation of the effects of stress on the usual breeding behaviour of birds in captivity, or an effect of the confined conditions resulting in a greater number of opportunities for extra-pair breeding activity to occur .…”
Section: Discussionsupporting
confidence: 90%
“…The high levels of extra-pair paternity and intraspecific broodparasitism recorded in our study were similar to other studies conducted in zebra finches in captive aviaries (Burley et al, 1996;Forstmeier et al, 2011;Schielzeth and Bolund, 2010;Tschirren et al, 2012), and considerably higher than levels recorded in the wild (Birkhead et al, 1990;. This difference may be a further manifestation of the effects of stress on the usual breeding behaviour of birds in captivity, or an effect of the confined conditions resulting in a greater number of opportunities for extra-pair breeding activity to occur .…”
Section: Discussionsupporting
confidence: 90%
“…The Zebra Finch is a classic avian study system for sexual selection and our results suggest that at least with respect to this character the domestication process has had no significant effect on the observed phenotypic variance (other characters such as ejaculate volume, sperm swimming speed and longevity remain to be studied). Birkhead 2010, Forstmeier et al 2011, Tschirren et al 2012, where the amenability of the species to experimental research will continue to provide an excellent opportunity for intensive behavioural and physiological study. Our findings are important because we have demonstrated that the rather unexpectedly high level of variance in sperm morphometry first described in a domestic population of Zebra Finches is not an artefact of captivity or the domestication process (Calhim et al 2007, Immler et al 2008, Kleven et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…There was also support for cytoplasmically inherited variance (2.4 ± 1.5% of phenotypic variance), consistent with an influence of mitochondrial variation on carotenoidbased color expression. Since a maternal effect term was included in the model, the cytoplasmic 345 inheritance effect is not expected to be confounded with single-generation, maternally inherited factors (e.g., egg size and composition: Tschirren et al 2012). Overall, non-autosomal sources of heritable variation were estimated to account for 9.1 ± 3.5% of phenotypic variance and to represent 25.4 ± 9.4% of the total heritable variance in beak coloration.…”
Section: Zebra Finchesmentioning
confidence: 99%